RNA biology takes root in plant systems. (6th September 2022) - Yu, David; McKinley, Lauren; Nien, Yachi; Prall, Wil; Zvarick, Allison
Abstract: Advances in RNA biology such as RNAi, CRISPR, and the first mRNA vaccine represent the enormous potential of RNA research to address current problems. Additionally, plants are a diverse and undeniably essential resource for life threatened by climate change, loss of arable land, and pollution. Different aspects of RNA such as its processing, modification and structure are intertwined with plant development, physiology and stress response. This report details the findings of researchers around the world during the 23rd Penn State Symposium in Plant Biology with a focus in RNA biology.